2009
DOI: 10.1189/jlb.1107753
|View full text |Cite
|
Sign up to set email alerts
|

BTLA targeting modulates lymphocyte phenotype, function, and numbers and attenuates disease in nonobese diabetic mice

Abstract: The novel coinhibitory receptor BTLA may have a regulatory role in maintaining peripheral tolerance; however, its role in autoimmune diabetes is unknown. In this study, we show that anti-BTLA mAb 6F7 selectively depleted pathogenic B and CD4+ T(H) cells; enhanced the proportion of cells with the forkhead box p3+ PD-1+CD4+ regulatory T phenotype; and increased the production of potentially protective (IL-10) and detrimental (IL-2, IFN-gamma) cytokines in NOD mice. As interactions between BTLA and PD-1 coinhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
0
26
1
Order By: Relevance
“…Triggering BTLA or deleting BTLA highly positive T cells also might have therapeutic significance. In a model of cerebral malaria, we have shown that an agonistic Ab can prevent experimental cerebral malaria (14) and others have shown that anti-BTLA can induce delayed onset of diabetes (15), decreased T cell-induced colitis (6), and prolonged allograft survival (15,16).…”
mentioning
confidence: 95%
“…Triggering BTLA or deleting BTLA highly positive T cells also might have therapeutic significance. In a model of cerebral malaria, we have shown that an agonistic Ab can prevent experimental cerebral malaria (14) and others have shown that anti-BTLA can induce delayed onset of diabetes (15), decreased T cell-induced colitis (6), and prolonged allograft survival (15,16).…”
mentioning
confidence: 95%
“…As a positive control, we included a de pleting murine antiBTLA antibody, 6F7 Truong et al, 2009). CFSElabeled donor cells were trans ferred into WT recipients that also received PIP, 6A6, or 6F7 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…There are a growing number of inhibitory receptors described, including CTLA-4, PD-1, BTLA, LAG-3, and CD160. In this issue of the Journal of Leukocyte Biology, a paper by Truong et al [1] examines the influence of anti-BTLA and anti-PD-1 antibodies on the disease progression in a model of autoimmune diabetes. This paper emphasizes the complexity involved in developing therapeutic antibody-based regimens to regulate immune responses using in vivo models and highlights the importance of understanding the function of these antibodies.…”
mentioning
confidence: 98%